Depletion of A-type lamins and Lap2α reduces 53BP1 accumulation at UV-induced DNA lesions and Lap2α protein is responsible for compactness of irradiated chromatin - Bártová, Eva; Legartová, Soňa; Krejčí, Jana; Řezníčková, Petra; Kovaříková, Alena Svobodová; Suchánková, Jana; Fedr, Radek; Smirnov, Evgeny; Hornáček, Matúš; Raška, Ivan (Journal of cellular biochemistry, 2018)
We studied how deficiency in lamins A/C and lamina-associated polypeptide 2α (Lap2α) affects DNA repair after irradiation. A-type lamins and Lap2α were not recruited to local DNA lesions and did not accumulate to γ-irradiation-induced foci (IRIF), as it is generally observed for well-known marker of DNA lesions, 53BP1 protein. At micro-irradiated chromatin of lmna double knockout (dn) and Lap2α dn cells, 53BP1 protein levels were reduced, compared to locally irradiated wild-type counterpart. Decreased levels of 53BP1 we also observed in whole populations of lmna dn and Lap2α dn cells, irradiated by UV light. We also studied distribution pattern of 53BP1 protein in a genome outside micro-irradiated region. In Lap2α deficient cells, identical fluorescence of mCherry-tagged 53BP1 protein was found at both microirradiated region and surrounding chromatin. However, a well-known marker of double strand breaks, γH2AX, was highly abundant in the lesion-surrounding genome of Lap2α deficient cells. Described changes, induced by irradiation in Lap2α dn cells, were not accompanied by cell cycle changes. In Lap2α dn cells, we additionally performed analysis by FLIM (Fluorescence Lifetime Imaging Microscopy) that showed different dynamic behavior of mCherry-tagged 53BP1 protein pools when it was compared with wild-type (wt) fibroblasts. This analysis revealed three different fractions of mCherry-53BP1 protein. Two of them showed identical exponential decay times (τ1 and τ3), but the decay rate of τ2 and amplitudes of fluorescence decays (A1-A3) were statistically different in wt and Lap2α dn fibroblasts. Moreover, γ-irradiation weakened an interaction between A-type lamins and Lap2α. Together, our results demonstrate how depletion of Lap2α affects DNA damage response (DDR) and how chromatin compactness is changed in Lap2α deficient cells exposed to radiation.
Keywords: DNA vazebné proteiny; oprava DNA; záření gama; Animals; Luminescent Proteins; DNA Damage; Gamma Rays; FRAP; Embryo, Mammalian; Fibroblasts; Recombinant Fusion Proteins; Chromatin; reportérové geny; Cell Line, Transformed; rekombinantní fúzní proteiny; Lamin Type A; Mice; lamin typ A; Ultraviolet Rays; membránové proteiny; signální transdukce; fibroblasty; DNA Repair; myši; Signal Transduction; Tumor Suppressor p53-Binding Protein 1; regulace genové exprese; poškození DNA; luminescentní proteiny; 53BP1; chromatin; DNA-Binding Proteins; Fluorescence Recovery After Photobleaching; Membrane Proteins; histony; Histones; Gene Expression Regulation; zvířata; Genes, Reporter; transformované buněčné linie; embryo savčí; ultrafialové záření